Ativo intangível com evidenciação contábil e desempenho dos clubes de futebol brasileiros e europeus - Maia, Anna Beatriz Grangeiro Ribeiro (2013)
The football market has assumed great proportions over time and secured their place in the world market, making it a business as profitable as other investments as the housing market, with the principles of profit maximization and the adoption of strategic technical and financial arrangements for administrative management. According to the Resource Based View of the Firm (RBV), of resources that can facilitate business performance, stand out intangible assets - category that fits the most representative of the assets of football clubs, according to the indications literature.Despite the mandatory accounting records in many countries, national and international studies show that the disclosure of intangible assets in the financial statements of entities in general, and especially in sports entities, has been superficial, not including all items required by accounting standards, implying a low quality informational entities in the accounting reports of this type of asset. Based on the arguments offered in the literature on fledgling accounting disclosure of intangible assets for the sports entities, the present study aimed to investigate patterns of association between intangible assets with accounting disclosure and economic performance of brazilian and european soccer clubs listed on the Club World Ranking. Regarding the methodological procedures, this research is classified as exploratory-descriptive as to the objectives; documental and bibliographical, as to the techniques; and predominantly quantitative, on the approach of the problem. The sample meets football clubs listed in the Club World Ranking 2012, of natural countries that adopt IFRS, based on the criteria of publication of the financial statements 2011. About the principal proxies, the variables were used: as intangible assets with accounting disclosure, Return of Intangible Assets (AIG) and the Representation of Intangible Assets (RAI); as economic performance, Return on Assets (ROA) and Return on Equity (ROE); and as sports performance, the classification sample according to the Ranking. The results of the quantitative analysis, show that: (i) the clubs were grouped into six clusters, and three most important factors are presented in order of discriminant power AIG, Des. Sports and ROE (ii) there are differences in the profile of intangible assets with accounting disclosure between european and brazilian clubs, particularly for the RAI (iii) there are no differences in the profile of economic performance for both ROE so as ROA to general, as well as between european and brazilian clubs, (iv) there is no correlation patterns between sports performance and profile of intangible assets with accounting disclosure in general, as well as between european and brazilian clubs. More timely, there is no correlation between the profile of intangible assets with accounting disclosure (AIG and RAI) of the clubs and their economic performance (ROE and ROA), although it has been identified negative correlation between AIG and ROE unexpected, the which raises new researches. From the above, according to the results of the data analysis of brazilian and european clubs, it is concluded that: there is no association between intangible assets with accounting disclosure and economic performance of the clubs in general, as well as between european and brazilian clubs, the profile of intangible assets with accounting disclosure brazilian clubs is different from the european, and the economic performance of the brazilian football clubs is similar to that of europeans.